Pengaruh Leverage Ratio, Likuidity Ratio, dan Sales Growth Ratio terhadap Financial Distress Bank Umum Syariah Tahun 2016-2020 - Siti Aisyah; Nurhayati (Bandung Conference Series: Accountancy, 2022)
Abstract. This research began with the phenomena of financial conditions having an effect on Islamic banking as a result of the corona virus pandemic, or Covid-19, in March 2020. The goal of this study was to ascertain the size of the Leverage Ratio (LVR), Liquidity Ratio (LKR), and Sales Growth Ratio (SGR) on the Financial Distress of Islamic Commercial Banks between 2016 and 2020. The LVR variable is calculated using the Debt to Equity Ratio, the LKR variable uses the Current Ratio, and the SGR variable uses the Sales Growth Ratio. The sample includes up to 11 Islamic Commercial Banks that are registered with the Financial Services Authority and have provided the essential information in an annual report published between 2016 and 2020. 55 samples were obtained in this study based on the sample size and range of observations. The research strategy employed is one of verification with a quantitative approach. Multiple regression analysis will be used to examine the stated hypothesis. The findings of this study reveal that LKR and SGR both have an influence on financial distress, however LVR has no effect. Abstrak. Penelitian ini berawal dari fenomena kondisi keuangan yang berpengaruh terhadap perbankan syariah akibat pandemi virus corona, atau Covid-19, pada Maret 2020. Tujuan dari penelitian ini adalah untuk memastikan besar kecilnya Leverage Ratio (LVR), Rasio Likuiditas (LKR), dan Rasio Pertumbuhan Penjualan (SGR) pada Financial Distress Bank Umum Syariah (BUS) periode 2016 hingga 2020. Variabel LVR dihitung menggunakan Debt to Equity Ratio, variabel LKR menggunakan Current Ratio, dan SGR variabel menggunakan Rasio Pertumbuhan Penjualan. Sampel mencakup hingga 11 BUS yang terdaftar di Otoritas Jasa Keuangan (OJK) dan telah memberikan informasi penting dalam laporan tahunan yang diterbitkan antara 2016 dan 2020. 55 sampel diperoleh dalam penelitian ini berdasarkan ukuran sampel dan rentang pengamatan. Strategi penelitian yang digunakan adalah salah satu verifikatif dengan pendekatan kuantitatif. Analisis regresi berganda akan digunakan untuk menguji hipotesis yang dikemukakan. Temuan penelitian ini mengungkapkan bahwa LKR dan SGR sama-sama berpengaruh terhadap financial distress, namun LVR tidak berpengaruh.